Physiological relevance of fructose 2,6-bisphosphate in the regulation of spinach leaf pyrophosphate:fructose 6-phosphate 1-phosphotransferase. - Theodorou, M; Kruger, N (2001)
A major problem in defining the physiological role of pyrophosphate:fructose 6-phosphate 1-phosphotransferase (PFP, EC 2.7.1.90) is the 1,000-fold discrepancy between the apparent affinity of PFP for its activator, fructose 2,6-bisphosphate (Fru-2,6-P2), determined under optimum conditions in vitro and the estimated concentration of this signal metabolite in vivo. The aim of this study was to investigate the combined influence of metabolic intermediates and inorganic phosphate (Pi) on the activation of PFP by Fru-2,6-P2. The enzyme was purified to near-homogeneity from leaves of spinach (Spinacia oleracea L.). Under optimal in vitro assay conditions, the activation constant (Ka) of spinach leaf PFP for Fru-2,6-P2 in the glycolytic direction was 15.8 nM. However, in the presence of physiological concentrations of fructose 6-phosphate, inorganic pyrophosphate (PPi), 3-phosphoglycerate (3PGA), phosphoenolpyruvate (PEP), ATP and Pi the Ka of spinach leaf PFP for Fru-2,6-P2 was up to 2000-fold greater than that measured in the optimised assay and Vmax decreased by up to 62%. Similar effects were observed with PFP purified from potato (Solanum tuberosum L.) tubers. Cytosolic metabolites and Pi also influenced the response of PFP to activation by its substrate fructose 1,6-bisphosphate (Fru-1,6-P2). When assayed under optimum conditions in the gluconeogenic direction, the Ka of spinach leaf PFP for Fru-1,6-P2 was approximately 50 microM. Physiological concentrations of PPi, 3PGA, PEP, ATP and Pi increased Ka up to 25-fold, and decreased Vmax by over 65%. From these results it was concluded that physiological concentrations of metabolites and Pi increase the Ka of PFP for Fru-2,6-P2 to values approaching the concentration of the activator in vivo. Hence, measured changes in cytosolic Fru-2,6-P2 levels could appreciably alter the activation state of PFP in vivo. Moreover, the same levels of metabolites increase the Ka of PFP for Fru-1,6-P2 to an extent that activation of PFP by this compound is unlikely to be physiologically relevant.